Digestion and Transport across the Intestinal Epithelium Affects the Allergenicity of Ara h 1 and 3 but Not of Ara h 2 and 6. Issue 6 (25th January 2021) - Smits, Mark; Nooijen, Irene; Redegeld, Frank; de Jong, Aard; Le, Thuy‐My; Knulst, André; Houben, Geert; Verhoeckx, Kitty
Abstract : Scope: No accepted and validated methods are currently available which can accurately predict protein allergenicity. In this study, the role of digestion and transport on protein allergenicity is investigated. Methods and results: Peanut allergens (Ara h 1, 2, 3, and 6) and a milk allergen ( β ‐lactoglobulin) are transported across pig intestinal epithelium using the InTESTine model and afterward basophil activation is measured to assess the (remaining) functional properties. Additionally, allergens are digested by pepsin prior to epithelial transport and their allergenicity is assessed in a human mast cell activation assay. Remarkably, transported Ara h 1 and 3 are not able to activate basophils, in contrast to Ara h 2 and 6. Digestion prior to transport results in a significant increase in mast cell activation of Ara h 1 and 3 dependent on the length of digestion time. Activation of mast cells by Ara h 2 and 6 is unaffected by digestion prior to transport. Conclusions: Digestion and transport influences the allergenicity of Ara h 1 and 3, but not of Ara h 2 and 6. The influence of digestion and transport on protein allergenicity may explain why current in vitro assays are not predictive for allergenicity. Abstract : Current methods for in vitro allergenicity assessment use purified or recombinant proteins to assess allergenicity, which does not mimic the physiological situation. Digestion and epithelial transport affected protein allergenicity. Undigested Ara h 1 and 3 did not elicit reactivity after transport (A ) but did when digested prior to transport (B ). Ara h 2 and 6 reactivity is not affected.